The Impact of Prolonged, Constrained Computer Work on Cervical Spine Proprioception and Trapezius Muscle Activity: An Observational Study - Dr. P. N. Ruvanthika; Dr. Vijayakumar; Dr S Kalaivani (The Bioscan, 2026)
Objective: This observational study aimed to quantify the acute effects of a standardized 90-minute computer work session on cervical joint position sense (JPS) error and upper trapezius muscle activity in asymptomatic adults. Methods: Thirty-five office workers (mean age 29.4 ± 5.1 years) with no recent neck pain participated. Cervical JPS was assessed via head-mounted laser pointer for target-matching accuracy in flexion, extension, and rotation. Surface electromyography (sEMG) recorded normalized root-mean-square (RMS) activity from the bilateral upper trapezii during a standardized typing task. Measurements were taken pre-session (T0), immediately post-session (T1), and after a 15-minute break (T2). Results: A significant increase in mean cumulative JPS error was observed at T1 (4.7° ± 1.2°) compared to T0 (3.1° ± 0.9°; p<0.001). Error remained elevated at T2 (4.1° ± 1.1°; p=0.003 vs. T0). sEMG revealed a significant increase in normalized RMS activity in the dominant-side trapezius at T1 (15.4% ± 3.1% MVC) compared to T0 (12.1% ± 2.8% MVC; p=0.002). Asymmetry in muscle activity (dominant vs. non-dominant) also increased significantly at T1 (p=0.01). Conclusion: A single bout of prolonged computer work leads to measurable deficits in cervical proprioception and altered trapezius muscle activation patterns, which do not fully recover after a short break. These acute physiological changes may represent early, sub-clinical risk factors for the development of work-related musculoskeletal disorders. Keywords cervical proprioception, electromyography, trapezius muscle, computer work, occupational health, musculoskeletal disorders.